Health Beliefs and Husband’s Preparedness in Supporting Postpartum Contraceptive Use - Feriani, Pipit; Krisnawati, Komang Menik Sri; Ernawati, Rini; Winarti, Yuliani (Jurnal Kesehatan Masyarakat, 2025)
Use of postpartum contraceptives is critical to the prevention of unwanted pregnancies and enhancing maternal and child health. Yet, husbands’ support for the use of contraceptives is still low based on cultural beliefs and inadequate knowledge. It is important to understand how health belief influences husbands’ readiness in order to improve family planning. This study will analyze the association between health beliefs and husbands’ readiness to support postpartum contraceptive use. A cross-sectional correlational descriptive design was employed with 170 husbands of postpartum women in Samarinda, Indonesia. Consecutive sampling was used, and data were collected using validated tools modeled after the Health Belief Model (HBM) and a scale of a husband’s preparedness. The tools were found to have high reliability, with Cronbach’s alpha values ranging from 0.761 to 0.988. Data analysis included univariate descriptive statistics and Spearman’s rank correlation to quantify the relationship between preparedness and the health beliefs of husbands. Researchers found a significant positive relationship between preparedness and health beliefs of husbands in support of postpartum use of contraceptives (p = 0.01, r = 0.745). The greatest correlation was between perceived susceptibility and concern (r = 0.548, p = 0.00), then self-efficacy and concern (r = 0.534, p = 0.00). Husbands’ health beliefs play a crucial role in their willingness to support postpartum contraceptive use. Anchoring on education programs that reinforce health beliefs will enhance husbands’ participation in family planning.